Clostridium clariflavum: Key Cellulosome Players Are Revealed by Proteomic Analysis - Lior Artzi (American Society for Microbiology, 2015)
ABSTRACT Clostridium clariflavum is an anaerobic, cellulosome-forming thermophile, containing in its genome genes for a large number of cellulosomal enzyme and a complex scaffoldin system. Previously, we described the major cohesin-dockerin interactions of the cellulosome components, and on this basis a model of diverse cellulosome assemblies was derived. In this work, we cultivated C. clariflavum on cellobiose-, microcrystalline cellulose-, and switchgrass-containing media and isolated cell-free cellulosome complexes from each culture. Gel filtration separation of the cellulosome samples revealed two major fractions, which were analyzed by label-free liquid chromatography-tandem mass spectrometry (LC-MS/MS) in order to identify the key players of the cellulosome assemblies therein. From the 13 scaffoldins present in the C. clariflavum genome, 11 were identified, and a variety of enzymes from different glycoside hydrolase and carbohydrate esterase families were identified, including the glycoside hydrolase families GH48, GH9, GH5, GH30, GH11, and GH10. The expression level of the cellulosomal proteins varied as a function of the carbon source used for cultivation of the bacterium. In addition, the catalytic activity of each cellulosome was examined on different cellulosic substrates, xylan and switchgrass. The cellulosome isolated from the microcrystalline cellulose-containing medium was the most active of all the cellulosomes that were tested. The results suggest that the expression of the cellulosome proteins is regulated by the type of substrate in the growth medium. Moreover, both cell-free and cell-bound cellulosome complexes were produced which together may degrade the substrate in a synergistic manner. These observations are compatible with our previously published model of cellulosome assemblies in this bacterium. IMPORTANCE Because the reservoir of unsustainable fossil fuels, such as coal, petroleum, and natural gas, is overutilized and continues to contribute to environmental pollution and CO2 emission, the need for appropriate alternative energy sources becomes more crucial. Bioethanol produced from dedicated crops and cellulosic waste can provide a partial answer, yet a cost-effective production method must be developed. The cellulosome system of the anaerobic thermophile C. clariflavum comprises a large number of cellulolytic and hemicellulolytic enzymes, which self-assemble in a number of different cellulosome architectures for enhanced cellulosic biomass degradation. Identification of the major cellulosomal components expressed during growth of the bacterium and their influence on its catalytic capabilities provide insight into the performance of the remarkable cellulosome of this intriguing bacterium. The findings, together with the thermophilic characteristics of the proteins, render C. clariflavum of great interest for future use in industrial cellulose conversion processes.